Tocilizumab and Abatacept for the Treatment of Childhood Chronic Uveitis: A Monocentric Comparison Experience - Maccora, Ilaria; Abu Rumeileh, Sarah; Curci, Franco; de Libero, Cinzia; Marrani, Edoardo; Mastrolia, Maria Vincenza; Pagnini, Ilaria; Simonini, Gabriele (Frontiers in Pediatrics, 2022)
Background Our study aimed to evaluate the efficacy of Tocilizumab and Abatacept for treating Childhood Chronic non-infectious Uveitis (CCU), resistant to anti-tumor necrosis factor (anti-TNF) treatment. Methods This is a monocentric retrospective charts review study (January 2010–April 2021) recruiting CCU, refractory to anti-TNF. To be included, children should have active uveitis at the time of Tocilizumab (8 mg/kg, every 4 weeks) or Abatacept (10 mg/kg, every 4 weeks). The main outcome was the achievement of ocular remission on treatment defined as the absence of flares for ≥ 6 months. Results In this study, 18 patients with CCU (14 F), previously treated with Methotrexate and Adalimumab, were enrolled: 15 had juvenile idiopathic arthritis (JIA) (83.3%), 2 idiopathic (11.1%), and 1 Behçet (5.6%). Furthermore, ten patients received Abatacept and 8 patients received Tocilizumab. The mean duration of treatment on Abatacept was 31.6 months (SD ± 30.8), on Tocilizumab 25.25 months (SD ± 17.8). In total, 13 children (72.2%) achieved remission, with a better remission rate for the Tocilizumab group (8/8) compared to the Abatacept group (5/10) (χ2 5.53, p = 0.019). No difference was evaluated between the two groups in the proportion of patients who showed flares during the treatment (2/6 Abatacept vs. 1/8 Tocilizumab). A significant difference was evaluated in the proportion of patients who flared after treatment discontinuation: 3/3 Abatacept vs. 0/3 Tocilizumab (χ2 3.8, p = 0.025). Conclusion Even though this is a monocentric retrospective study, in a relatively small group, our study suggests a superior efficacy of Tocilizumab over Abatacept for treating anti-TNF refractory CCU.